Toward a global civil society - Walzer, Michael (International political currents, 1995)
The demise of Communism has not only affected Eastern Europe but also the countries of the West where a far-reaching examination of political and economic systems has begun. This collection of essays by internationally renowned scholars of political theory from Europe and the United States explores both the concept and the reality of civil society and its institutions.